Dear Hank Williams - Holt, Kimberly Willis (Henry Holt and Company, 2015)
In Rippling Creek, Louisiana, in 1948, eleven-year-old Tate writes letters to her favorite country singer, sharing her dreams of becoming a singer and revealing that her mother is in prison.